2018
DOI: 10.1177/1094428118802626
|View full text |Cite
|
Sign up to set email alerts
|

Experience Sampling Methods: A Discussion of Critical Trends and Considerations for Scholarly Advancement

Abstract: In the organizational sciences, scholars are increasingly using experience sampling methods (ESM) to answer questions tied to intraindividual, dynamic phenomenon. However, employing this method to answer organizational research questions comes with a number of complex—and often difficult—decisions surrounding: (1) how the implementation of ESM can advance or elucidate prior between-person theorizing at the within-person level of analysis, (2) how scholars should effectively and efficiently assess within-person… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
559
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 502 publications
(645 citation statements)
references
References 157 publications
16
559
1
Order By: Relevance
“…Following the recommendations of Gabriel et al. (), we included two additional sets of control variables to eliminate potential artifactual explanations for our results. First, we controlled for the prior measurement of each endogenous construct and the day of the study.…”
Section: Study 1 Methodsmentioning
confidence: 99%
“…Following the recommendations of Gabriel et al. (), we included two additional sets of control variables to eliminate potential artifactual explanations for our results. First, we controlled for the prior measurement of each endogenous construct and the day of the study.…”
Section: Study 1 Methodsmentioning
confidence: 99%
“…Despite several strengths of our studies, such as the field‐experimental nature of Study 1 and the replication of our model at both the within‐ and between‐person levels (Gabriel et al., ), our studies have several limitations that provide exciting avenues for future research. First, although we manipulated powerlessness, all other variables in our model were self‐reported, which raises potential concerns associated with common method and source bias (Podsakoff, MacKenzie, Lee, & Podsakoff, ).…”
Section: Discussionmentioning
confidence: 97%
“…First, although we manipulated powerlessness, all other variables in our model were self‐reported, which raises potential concerns associated with common method and source bias (Podsakoff, MacKenzie, Lee, & Podsakoff, ). Scholars have suggested that in experience sampling studies (such as the one employed in Study 1), participants are in the best position to rate their own behaviors, as no other employee is in a position to observe all interactions a participant has with others throughout the day (Courtright, Gardner, Smith, McCormick, & Colbert, ; Foulk et al., ; Gabriel et al., ). Furthermore, recent research that has compared self‐reported and other‐reported daily behaviors has found that both ways of measuring employee behaviors exhibit comparable accuracy (Vazire & Mehl, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations